Vínculos com a organização e os estilos de liderança: uma análise na equipe de enfermagem de instituições hospitalares - Santos, Andressa Schaurich dos (2015)
This study aimed to analyze the relationship between the ties of workers with the organization and the leadership styles of managers in Public and Private Hospitals Nursing team in Rio Grande do Sul (RS). Therefore, we carried out a case study, descriptive and quantitative approach nature. The research sample consisted of 347 nurses, technicians and nursing assistants from a public and a private hospitals, located in the city of Porto Alegre/RS. To collect data, we used a research protocol (questionnaire) with closed items, divided into three parts: personal and occupational data; Ties to the Organization; and Leadership styles. Data analysis was performed using the software "Microsoft Excel" version 2010, SPSS version 18 and SAS version 9.1, by calculating descriptive statistics, groups comparison of techniques and correlation analysis - Pearson correlation coefficient. The data obtained in the analysis revealed that the correlations between the constructs all associations were positive, which indicates there is some form of direct relation between them. Considering the relationship between "Ties with the Organization" and "Leadership Styles" concluded for the study context, the Organizational Commitment correlated more strongly with the Transformational Leadership and its Intellectual Stimulation basis, as Organizational Consent also bound more strongly with this leadership and its base Charisma or Idealized Influence. At the same time, the Organizational Entrenchment was related significantly only with Leadership Absence, showing that, on this link, very little is perceived by employees as of leadership responsibility. From these results, we can say that the ties that workers develop with their organizations are related to leadership styles of their managers, or the absence of these, some with a stronger intensity, other weaker, but all positively associated.